Steroid pretreatment of organ donors does not impact on early rejection and long‐term kidney allograft survival: Results from a multicenter randomized, controlled trial. Issue 6 (1st February 2019) - Reindl‐Schwaighofer, Roman; Kainz, Alexander; Jelencsics, Kira; Heinzel, Andreas; Berlakovich, Gabriela; Remport, Ádám; Heinze, Georg; Langer, Robert; Oberbauer, Rainer
Abstract : Steroid pretreatment of deceased donors reduces inflammation in allografts and is recommended by organ procurement guidelines. The impact on long‐term graft outcome, however, remains elusive. In this multicenter randomized controlled trial, 306 deceased donors providing organs for 455 renal transplant recipients were randomized to 1000 mg of methylprednisolone or placebo prior to organ procurement (ISRCTN78828338). The incidence of biopsy‐confirmed rejection (Banff>1) at 3 months was 23 (10%) in the steroid group and 26 (12%) in the placebo group ( P  = .468). Five‐year functional graft survival was 84% and 82% for the steroid group and placebo group, respectively ( P ‐value = .941). The hazard ratio of functional graft loss was 0.90 (95% confidence interval 0.57‐1.42, P  = .638) for steroid vs placebo in a multivariate Cox model. We did not observe effect modification by any of the predictors of graft survival and treatment modality. A robust sandwich estimate was used to account for paired grafts of some donors. The mean estimated GFR at 5 years was 47 mL/min per 1.73 m 2 in the steroid group and 48 mL/min per 1.73 m 2 in the placebo group ( P  = .756). We conclude that steroid pretreatment does not impact on long‐term graft survival. In a donor population with higher risk of delayed graft function, however, repetitive and higher doses of steroid treatment may result in different findings. Abstract : Steroid pretreatment of deceased organ donors using a single 1000 mg dose of methylprednisolone does not reduce the incidence of biopsy‐confirmed acute rejection episodes within the first 3 months posttransplantation and does not improve 5‐year functional graft survival compared to placebo, despite reduction of inflammation signatures in preimplantation biopsies.